Iron overload in a murine model of hereditary hemochromatosis is associated with accelerated progression of osteoarthritis under mechanical stress - Camacho, A. (2017)
Objective: Hereditary hemochromatosis (HH) is a disease caused by mutations in the Hfe gene characterised by systemic iron overload and associated with an increased prevalence of osteoarthritis (OA) but the role of iron overload in the development of OA is still undefined. To further understand the molecular mechanisms involved we have used a murine model of HH and studied the progression of experimental OA under mechanical stress.Design: OA was surgically induced in the knee joints of 10-week-old C57BL6 (wild-type) mice and Hfe-KO mice. OA progression was assessed using histology, micro CT, gene expression and immunohistochemistry at 8 weeks after surgery.Results: Hfe-KO mice showed a systemic iron overload and an increased iron accumulation in the knee synovial membrane following surgery. The histological OA score was significantly higher in the Hfe-KO mice at 8 weeks after surgery. Micro CT study of the proximal tibia revealed increased subchondral bone volume and increased trabecular thickness. Gene expression and immunohistochemical analysis showed a significant increase in the expression of matrix metallopeptidase 3 (MMP-3) in the joints of Hfe-KO mice compared with control mice at 8 weeks after surgery.Conclusions: HH was associated with an accelerated development of OA in mice. Our findings suggest that synovial iron overload has a definite role in the progression of HH-related OA.